Preferring Reactivity over Proactivity: Exploring the Nature of Bangladeshi Print Media in Covering Environmental News - Sanjoy Basak Partha; Meherun Nahar (Asian Journal of Media and Communication, 2023)
Despite the continuous efforts made in recent years to improve environmental qualities, pollution still poses a serious threat to human health and harms the planet. Emphasizing the Sustainable Development Goals (SDG), Bangladesh is highly determined to achieve all its goals in due time. In this context, given Bangladesh’s current environmental situation, traditional media have a crucial role to play, especially in developing environmental awareness. This study investigates how Bangladeshi print media cover environmental issues and whether they practice proactive or reactive reporting to raise public awareness. There are two phases in this study, combining qualitative and quantitative methods. An analysis of the coverage and treatment of environmental news for one year, January to December 2022, in four major Bangladeshi newspapers, two each in Bengali and English, was accomplished in the first phase using content analysis. The second phase involved in-depth interviews with six senior environment-beat reporters. The study found that Bangladeshi mainstream newspapers are still far away from practicing proactive environmental reporting, as only one-fourth of the news reports are found to be proactive. The study also suggested some recommendations for the editorial body & policymakers.